Heart failure following cavopulmonary shunt - An unusual story of desmin cardiomyopathy - Lamk Kadiyani; Sivasubramanian Ramakrishnan; Sudheer Kumar Arava; Sandeep Seth (Wolters Kluwer Medknow Publications, 2024)
Partial cavopulmonary shunt is an established procedure for patients with abnormal right ventricular (RV) physiology. Late failure of the Glenn shunt is usually due to further progression of the primary disease process. However, there may be surprises, as in our patient. We report an 8-year-old child who was diagnosed with tricuspid valve (TV) dysplasia with borderline RV hypoplasia. He underwent TV repair with a right cavopulmonary shunt. He presented with features of heart failure after 6 years of the surgery. An echocardiographic evaluation suggested a restrictive filling pattern of the RV with preserved size and function. Computed tomography and cardiac magnetic resonance imaging revealed a normal pericardial thickness with no evidence of myocardial involvement. Despite the contradicting clinical and imaging features, endomyocardial biopsy confirmed a diagnosis of desmin cardiomyopathy. Restrictive cardiomyopathy may remain an elusive diagnosis despite extensive imaging. In our case, the altered loading conditions due to a cavopulmonary shunt further masked pathophysiological hemodynamic changes.